ANALYSIS OF THE RESULTS OF THE INITIAL OPERATION OF COTTON WITH HIGH MOISTURE IN COTTON CLEANING PLANTS - Parpiev Azim Parpievich; Sabirov Ilkhom Kakhromonovich; Abdullaev is the son of Sharofiddin Yuusup (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, the results of initial processing of high moisture cotton in cotton gins are analyzed. The results of initial processing of low-quality cotton in Gharam , quality storage, proper organization of long-term storage, layering taking into account humidity, otherwise, if the storage process is not properly organized, the effect of dirt and moisture on the results of initial processing of cotton was studied.